Regional Multicriteria and Multimodal Route Planning System for Public Transportation: A Case Study - Békési, József (Acta Cybernetica, 2018)
Nowadays, the use of computer-based route planners is popular among private and public transportation passengers. A large range of websites and GPS navigation devices provide such services for their users. Here, we present an algorithm used by a route planning system which operates on a complete public transport network of two regions from two countries, namely Hungary and Serbia. The algorithm can handle the pedestrian traffic between stops not too far from each other. It can take into account individual user preferences like walking distances and modes of transport. The graph representing the transport network was very large, but with the help of some speed-up techniques, we managed to create an effective search algorithm that is able to handle user requirements.